Good Pharmacy Practice in Chronic Disease Management - Mahajan, Neelam (Indian Journal of Pharmacy Practice)
Chronic diseases have been reported to be leading cause of death in world. The WHO report had proposed the global goal to reduce the projected trend of chronic disease death rates by 2% by 2015. Various individual, institutional & organizational healthcare interventions in academic, hospital and community settings are required and have been reported to achieve this aim. Ironically, the provision of pharmaceutical care to the patient of chronic diseases by community pharmacist in community settings had remained a far reality on one hand and on the other hand the escalating healthcare costs, unstable disease state, changing disease patterns, multiple complications requiring administration of multiple drugs ,complex dosage regimens, non compliance to therapy, associated multiple psycho social problems make chronic disease and chronic disease therapy management problematic. Quality of life of the chronic disease patients and reduction of chronic disease death rates depends not only on the quality of drugs supplied by community pharmacies but also on the necessary psycho social support and pharmaceutical care of pharmacist. It is proposed that, community pharmacies should be projected as places where the chronic disease patients can get pharmaceutical care. Adherence to good pharmacy practices by community pharmacies is viable intervention required to maintain the quality of therapy received by the patients of chronic diseases.
Keywords: Chronic diseases; pharmaceutical care; Quality of life